Lignans Isolated From Flower Buds of Magnolia fargesii Attenuate Airway Inflammation Induced by Cigarette Smoke in vitro and in vivo - Lee, Su-Ui; Ryu, Hyung Won; Lee, Seoghyun; Shin, In-Sik; Choi, Ji-Hee; Lee, Jae-Won; Lee, Jinhyuk; Kim, Mun Ock; Lee, Hyun-Jun; Ahn, Kyung-Seop; Hong, Sung-Tae; Oh, Sei-Ryang (Frontiers in Pharmacology, 2018)
The flower buds of Magnolia fargesii, known traditionally as Xinyi, exert anti-inflammatory effects against inflammatory lung diseases such as chronic obstructive pulmonary disease (COPD). Lignans isolated from Xinyi are an important group of plant-derived anti-inflammatory compounds. However, the mechanisms of action underlying their protective effects against COPD are not yet fully understood. Here, we showed that seven lignans (lignans 1-7) obtained from a CHCl3 fraction of Xinyi effectively suppress the inflammatory response in cigarette smoke condensate (CSC)-stimulated airway epithelial cells (in vitro) and in a mouse model of COPD established by exposure to cigarette smoke (CS) and lipopolysaccharides (LPS). The CHCl3 fraction was found to inhibit CSC-induced IL-6 expression in human airway epithelial cells, and to suppress the infiltration of inflammatory cells (neutrophils and macrophages) and secretion of inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in the mouse model. Similarly, each of the seven lignans isolated from the CHCl3 fraction also suppressed the infiltration of inflammatory cells (neutrophils and macrophages) and secretion of inflammatory mediators such as reactive oxygen species (ROS), TNF-α, and IL-6 in vivo. Notably, all lignan compounds significantly suppressed both extracellular signal-related kinase (ERK) and Akt phosphorylation levels in CSC-stimulated human lung mucoepidermoid carcinoma (NCI-H292) cells. Of these, lignan 1 (dimethylpinoresinol) inhibited the expression of CSC-induced inflammatory cytokines (IL-1β, -6 and -8) in vitro in a dose-dependent manner by suppressing the activation of epidermal growth factor receptor (EGFR) and its downstream effectors, including ERK and Akt, in NCI-H292 cells. Our results show that the lignans isolated from Xinyi may prevent airway inflammatory diseases through the suppression of EGFR and its downstream effectors.